INDUCED POLARIZATION MEASUREMENTS ON UNSATURATED, UNCONSOLIDATED SANDS - Ulrich C.; Slater L. (My University, 2004)
Induced polarization (IP) measurements were obtained on unsaturated, unconsolidated sediments during (1) evaporative drying and (2) pressure drainage followed by subsequent imbibition (water reentry). Porous ceramic discs were used with existing laboratory IP instrumentation to permit accurate IP measurements on unsaturated samples. Polarization magnitude during evaporative drying approximates a power law dependence on saturation. Saturation exponents for the polarization term were consistently less than Archie conduction exponents, although no clear relationship between the exponents was observed. The polarization measured over a pressure drainage and imbibition cycle exhibits a complex (yet similar between tested samples) saturation dependence, being a function of saturation range and saturation history. Polarization is observed to increase with saturation over certain saturation intervals, yet decrease with saturation over others. High polarization observed during sample imbibition is consistent with a model for the development of a continuous charged air-fluid interface as previously proposed to explain hysteresis in resistivity measurements. The saturation dependence of the phase angle measured in IP in large part results from changes in conduction as pores fill and drain. Models of low-frequency polarization based on grain-size-controlled and pore-size-controlled relaxation both support dependence of IP measurements on saturation. Our results suggest that saturation dependent polarization must be considered for effective interpretation of IP measurements from the vadose zone. © 2004 Society of Exploration Geophysicists. All rights reserved.